An Analysis of the Bidirectional LMS Algorithm over Fast-Fading Channels - Yapici, Y.; Yilmaz, A. O. (IEEE transactions on communications, 2012)
A bidirectional LMS algorithm is considered for estimation of fast frequency-selective time-varying channels with a promise of near optimal tracking performance and robustness to parameter imperfections under various scenarios at a practical level of complexity. The performance of the algorithm is verified by the theoretical steady-state MSE analysis and experimental bit error rate (BER) results.